Management system of drinking water quality in Poland - Radzka, Elżbieta; Jankowska, Jolanta (Management and Administration Journal, 2024)
Collective drinking water supply is carried out by water and sewage companies. They areobliged by law to ensure of water supply in a continuous way with adequate quality. Supervision of thewater quality intended for human consumption in Poland is be held State Sanitary Inspection.Systematic water control is carried out by the district sanitary inspector. District Sanitary--Epidemiological Station conducts control monitoring an average 4 times a year in each water supplywhile revision monitoring once a year.